COMPUTER SIMULATION OF TEMPERATURE DISTRIBUTION ON PULLED-OUT INGOT SURFACE AT DISCRETE CHARACTER OF SECONDARY COOLING ZONES - A. N. Chichko; N. V. Andrianov; A. V. Demin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
Computer calculations of tensile and compression stresses along an ingot length of 250´300 size for a group of industrial steel are conducted on the basis of the «ProNRS-2» computer system. New data about nature of surface stresses in industrial ingots of 40Х, 70К, 2С45, 20ХН3А steel grades are obtained. It is shown that the highest level of tensile stress is observed in the case of an ingot of 40X steel grade and the lowest level of this parameter is fallen at an ingot of 70К steel grade.